Rethinking scientists’ ongoing participation in “feeding the world” - Haring, Steven; Pesci Schmulevich, Sasha; Manser, Gwyneth M.; Cooper, Mark H. (Frontiers in Sustainable Food Systems, 2023)
Agricultural science necessarily involves a commitment to some form of humanitarian and environmental ethics. For the past century, agricultural science has been based on a productivist ethic of maximizing agricultural production in pursuit or support of food security. Recognition of the ethical and political disposition of contemporary agricultural science can help scientists reorient their work to better address the urgent problems of the upcoming century: environmental degradation, climate change, and social inequality. A commitment to solving these problems is well within the scope of modern agricultural science. Supporting and furthering multidimensional food systems should replace productivism as an explicit goal of agricultural development and scientific innovation.